The Societal Influences and Quality of Life Among Healthcare Team Members During the COVID-19 Pandemic - Kao, Wei-Tsung; Hsu, Su-Ting; Chou, Frank Huang-Chih; Chou, Li-Shiu; Hsieh, Kuan-Ying; Li, Dian-Jeng; Lin, Guei-Ging; Wu, Pay-Jen; Chen, Wei-Jen; Huang, Joh-Jong (Frontiers in Psychiatry, 2021)
Background: The corona virus infection disease 2019 (COVID-19) pandemic is likely to put healthcare professionals across the world in an unprecedented situation. Methods: 683 healthcare workers were recruited in this study. Short form-12 items (SF-12), Societal Influences Survey Questionnaire (SISQ), and Disaster-Related Psychological Screening Test (DRPST) were used to survey participants. Multiple linear regression and structural equation model (SEM) were used to explore the possible factors to the societal influences and quality of life. Results: After Multiple linear regression analysis, female, older, more education years, married, regular intake and posttraumatic stress disorder (PTSD) frequency had positive association with SISQ. To physical component summary (PCS) of SF-12, chronic illness, sleep score, PTSD frequency and social distance had negative association and exercise habits had positive association. To mental component summary (MCS) value of SF-12, age, participate in social activities and social information had positive association and PTSD frequency, sleep score, social anxiety and depression had negative association. Under SEM analysis, PTSD had positive influence on SISQ. Sleep score and MCS value had negative influences on SISQ. PTSD severity, older age, Sleep score, smoking and Nursing staff had negative influences on PCS value. Young age, PTSD frequency, sleep score and depression had negative influences on MCS value. Conclusion: Healthcare team members with severer PTSD symptoms suffered more societal influences. Relative to PTSD severity, PTSD frequency was more important to the quality of life. Members of older age, who frequently participate in clubs, volunteers or charity activities had better mental life quality.